THE POLITICS OF MULTICULTURALISM OF THE TOWANI TOLOTANG MINORITY IN SOUTH SULAWESI - Zuly Qodir (Al-Albab, 2013)
This article provides a description of the ethnographical and political issues of the minority group located in South Sulawesi, i.e. the believers of Towani Tolotang that still exist there even in the national political scene as they have representatives in the legislature. The community seems to be playing the politics of Towani Tolotang accommodating and making use of the will of the political regime of Muslims and Hindus, where both of them are scrambling for mutual acknowledgment and entering into the tradition of the religion: Islam or Hinduism. As a minority group, the Towani Tolotang community has a variety of strategies to survive and fight in various kinds of interest. Economic and political gain, and commodification of ethnicity and religion are rampant in the area due to decentralization. This article is based on field library and research on the minority people who have been dealing with political suppression and discriminatory treatment. Keywords: Towani, Tolotang and minority, political rights.